HIV-1 Productively Infects and Integrates in Bronchial Epithelial Cells - Devadoss, Dinesh; Singh, Shashi P.; Acharya, Arpan; Do, Kieu Chinh; Periyasamy, Palsamy; Manevski, Marko; Mishra, Neerad; Tellez, Carmen S.; Ramakrishnan, Sundaram; Belinsky, Steven A.; Byrareddy, Siddappa N.; Buch, Shilpa; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
Background: Role of lung epithelial cells in HIV-1-related lung comorbidities remains unclear and major hurdle in curing HIV is the persistence of latent HIV reservoirs in people living with HIV (PLWH). The advent of combined antiretroviral therapy has considerably increased the life span; however, the incidence of chronic lung diseases is significantly higher among PLWH. Lung epithelial cells orchestrate the respiratory immune responses and whether these cells are productively infected by HIV-1 is debatable. Methods: Normal human bronchial epithelial cells (NHBEs) grown on air-liquid interface were infected with X4-tropic HIV-1LAV and examined for latency using latency-reversing agents (LRA). Role of CD4 and CXCR4 HIV coreceptors in NHBEs were tested and DNA sequencing analysis was used to analyze the genomic integration of HIV proviral genes, Alu-HIVgag-pol, HIV-nef, and HIV-LTR. Lung sections from HIV-infected humans and SHIV-infected macaques were analyzed by FISH for HIV-gag-pol RNA and epithelial cell-specific immunostaining. Results & Discussion: NHBEs express CD4 and CXCR4 at higher levels than A549 cells. NHBEs are infected with HIV-1 basolaterally, but not apically, by HIV-1 in a CXCR4/CD4-dependent manner leading to HIV-p24 production; however, NHBEs are induced to expressed CCR5 by IL-13 treatment. In the presence of cART, HIV-1 induces latency and integration of HIV-provirus in the cellular DNA, which is rescued by the LRAs (endotoxin/vorinostat). Furthermore, lung epithelial cells from HIV-infected humans and SHIV-infected macaques contain HIV-specific RNA transcripts. Thus, lung epithelial cells are targeted by HIV-1 and could serve as potential HIV-reservoirs that may contribute to the respiratory comorbidities in PLWH.